2019
DOI: 10.1002/cptc.201900112
|View full text |Cite
|
Sign up to set email alerts
|

Potential‐Energy Surface and Dynamics Simulation of THBDBA: An Annulated Tetraphenylethene Derivative Combining Aggregation‐Induced Emission and Switch Behavior

Abstract: Electronic structure calculations and nonadiabatic dynamics simulations were carried out on the excited state decay mechanism of a typical aggregation-induced emission (AIE)active molecule, 10,10',11,11'-tetrahydro-5,5'-bidibenzo[a,d][7] annulenylidene (THBDBA), which was experimentally found to be almost non-emissive in THF solution but highly luminescent as an aggregate. At the MS-CASPT2//CASSCF level, the decay path from S 1 leads to a conical intersection (CI) seam with the ground state (S 0 ) via a cycliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Thus, to account for the AIE phenomena in BPAs, it is necessary to consider the contributions from the restriction of decay path through an S 0 /S 1 -MECI in the solid phase. [60] The electronic structure for the first excited state in solution is quite similar to that for the solid phase as demonstrated by the calculated reorganization energy. As shown in Figure 1, the reorganization energy of 9,10-BPA slightly decreases from 6384 to 5202 cm −1 from the solution phase to the solid phase due to a more rigid environment upon aggregation.…”
Section: Rate Constants By Thermal Vibration Correlation Functionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, to account for the AIE phenomena in BPAs, it is necessary to consider the contributions from the restriction of decay path through an S 0 /S 1 -MECI in the solid phase. [60] The electronic structure for the first excited state in solution is quite similar to that for the solid phase as demonstrated by the calculated reorganization energy. As shown in Figure 1, the reorganization energy of 9,10-BPA slightly decreases from 6384 to 5202 cm −1 from the solution phase to the solid phase due to a more rigid environment upon aggregation.…”
Section: Rate Constants By Thermal Vibration Correlation Functionsupporting
confidence: 57%
“…Thus, to account for the AIE phenomena in BPAs, it is necessary to consider the contributions from the restriction of decay path through an S 0 /S 1 –MECI in the solid phase. [ 60 ]…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown in the previous section that the parent molecule ( PDP ) does not reach a higher excited state than S 1 when irradiated at 350 nm. In this section, we have investigated the excitation properties of the carbene intermediate and excited state intramolecular proton transfer (ESIPT) or rearrangements in excited states (RIES) …”
Section: Resultsmentioning
confidence: 99%
“…In general, the emission quantum yield is an essential index for organic luminescent materials, but it cannot be quantitatively predicted based on the FE profile alone. However, for isolated AIE-gen systems, many computational studies have confirmed that transitions from the photoexcited state to the ground state can proceed when the CIs of the molecules are energetically accessible. , ,,, The FE profile illustrated in Figure a shows that the conformational change of DPDBF from the FC to the MECI in acetonitrile solution is energetically acceptable, as is the case in the isolated state. Therefore, after photoexcitation, DPDBF dissolved in acetonitrile solution spontaneously reaches the CIs through the excited-state relaxation process, resulting in fluorescence quenching.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism responsible for AIE has been investigated both experimentally and theoretically. The restriction of intramolecular motions has been used as a general concept to explain why aggregation induces fluorescence emission from AIE-gens. ,,,, In particular, when focusing on the role of conical intersections (CIs), the concept of restricted access to a CI has been introduced to understand the AIE mechanism from a theoretical point of view. ,, Many computational studies have contributed to establishing a conceptual basis for the AIE mechanism, mainly by elucidating the quenching pathways of AIE-gens in an isolated state. ,, For example, in the case of DPDBF, the internal rotation of the ethylenic CC π-bond, labeled θ in Figure , may play a key role in AIE. Previous computational studies have revealed that the electronic ground (S 0 ) and first singlet excited (S 1 ) states of DPDBF with a twisted geometry about the ethylenic CC bond have the same energy and intersect each other to form CIs .…”
Section: Introductionmentioning
confidence: 99%